SIRT5 participates in the suppressive tumor immune microenvironment of EGFR-mutant LUAD by regulating the succinylation of ACAT1 - Wang Shouhan; Li Qingchang; Sun Xiaodan (Heliyon)
Epidermal growth factor receptor (EGFR)-mutant lung adenocarcinoma (LUAD) exhibits a poor response to immune checkpoint inhibitors (ICIs) by shaping a suppressive tumor immune microenvironment (TIME), which characters as lacking immune cell infiltration; however, the underlying mechanism remains to be elucidated. Here, we demonstrated that Sirtuin 5 (SIRT5), a member of the deacetylase SIRT family, functions as a desuccinylase of acetyl-CoA acetyltransferase 1 (ACAT1) and enhances the enzymatic activity of ACAT1 to activate the NRF2 pathway, inhibiting the secretion of the chemokines CCL5 and CXCL10, which are important for recruiting CD8+ T cells, thereby participating in the formation of an inhibitory TIME in EGFR-mutant LUAD. In conclusion, we propose that the combination of a SIRT5 inhibitor with ICIs therapy may be a promising therapeutic approach for patients with EGFR-mutant LUAD.